2008
DOI: 10.1021/jp801695x
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Electronic Spectroscopy To Examine Shock-Wave-Induced Changes in Anthracene Single Crystals

Abstract: Shock-wave-induced electronic structure changes in anthracene single crystals were examined using timeresolved absorption and fluorescence spectroscopy. Crystals were subjected to stepwise loading normal to the (001) crystallographic plane to peak stresses between 2.5 and 6.0 GPa. Absorption experiments revealed (i) a monotonic shift of the absorption edge of the singlet state toward lower energies (red shift) and (ii) formation of a new band on the lower energy side of the red-shifted absorption edge. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Therefore, in studies of molecular crystals under high pressure, some of the observed effects might not be related to pressure, but rather to stress deviators, and, consequently, to crystal deformation. Also, studies under intentionally introduced nonhydrostaticity, as was done here, can provide further insight into processes occurring under shock compression where nonhydrostatic conditions are the norm …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, in studies of molecular crystals under high pressure, some of the observed effects might not be related to pressure, but rather to stress deviators, and, consequently, to crystal deformation. Also, studies under intentionally introduced nonhydrostaticity, as was done here, can provide further insight into processes occurring under shock compression where nonhydrostatic conditions are the norm …”
Section: Discussionmentioning
confidence: 92%
“…Also, studies under intentionally introduced nonhydrostaticity, as was done here, can provide further insight into processes occurring under shock compression where nonhydrostatic conditions are the norm. 39…”
Section: Discussionmentioning
confidence: 99%
“…Anthracene bulk crystals and/or thin films have been a long-time subject of the solid-state studies. The structure−property relationship has been well-established. It was reported that the optical and electronic properties of anthracene solids depend on a number of factors, such as the ordering of molecular arrangement, the structural defects, the existence of trace impurity and/or doped guest molecules, and the dimension of anthracene solids. Fabrication of one-dimensional nanostructures such as nanowires is of great implications in the applications of optoelectronic nanodevices. , However, as compared to the extensive studies of anthracene bulk crystals and/or thin films, the investigations of linear anthracene nanostructures are very rare. Liu et al synthesized anthracene nanowires through solid-phase reaction and found that they display fluorescence properties significantly different from those of anthracene bulk crystals.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Fabrication of one-dimensional (1D) nanostructures such as nanowires is of great implications in the applications of optoelectronic nanodevices. 41,42 However, compared to the extensive studies of anthracene bulk crystals and/or thin films, [43][44][45] the investigations of anthracene nanowires are exceptionally rare. Liu et al 40 recently reported the fabrication of anthracene nanowires through solid-phase reaction.…”
Section: Introductionmentioning
confidence: 99%